Physical activity and the aging brain effects of exercise on neurological function - Watson, Ronald R. (Ronald Ross) (London, United Kingdom San Diego, CA Academic Press, an imprint of Elsevier, 2017)
A complete guide to the manifold effects of exercise and physical activity on the aging brain. This book examines the role that exercise and physical activity play in halting or modulating the deleterious effects of these numerous aging concerns.
I. Overview of exercise and neurological changes. Effects of physical activity on the cerebral networks / A. Begega, P. Alvarez-Suarez, P. Sampedro-Piquero and M. Cuesta -- Exercise and the developing brain in children and adolescents / M.M. Herting and M.F. Keenan -- Differential expression of the brain proteome in physical training / T. Ravikiran, R. Vani and S. Anand -- Physical exercise-induced changes in brain temperature / A.C. Kunstetter, W.C. Damasceno, C.G. Fonseca and S.P. Wanner -- II. Drugs of abuse with exercise to modify neurological structure and function. Physical activity as a therapeutic intervention for addictive disorders : interactions with ethamphetamine / S.S. Somkuwar, M.J. Fannon-Pavlich and C.D. Mandyam -- Pharmacological intervention of brain neurotransmission affects exercise capacity / X. Zheng and H. Hasegawa -- The endocannabinoid system and chronic disease : opportunity for innovative therapies / A. Yoder -- III. Factors modulating exercise in aging and neurological consequences. Changes in cerebral blood flow during steady-state exercise / M. Hiura and T. Nariai -- Biochemical mechanisms associated with exercise-induced neuroprotection in aging brains and related neurological diseases / M.S. Shanmugam, W.M. Tierney, R.A. Hernandez, A. Cruz, T.L. Uhlendorf and R.W. Cohen -- Role of melatonin supplementation during strenuous exercise / J. Diaz-Castro, M. Pulido-Moran, J. Moreno-Fernandez, N. Kajarabille, S. Hijano and J.J. Ochoa -- IV. Exercises as therapy for neurological diseases. Mechanisms of functional recovery with exercise and rehabilitation in spinal cord injuries / M. Cowan and R.M. Ichiyama -- Neural structure, connectivity, and cognition changes associated to physical exercise / S. Bonativa and G. Tedeschi -- The effect of exercise on motor function and neuroplasticity in Parkinson's disease / J. Watson, K.E. Welman and B. Sehm -- Physical exercise and its effects on Alzheimer's disease / A.M. Stein and R.V. Pedroso -- Cortical reorganization in response to exercise / P. Stephane -- Exercise enhances cognitive capacity in the aging brain / S. Snigdha and G.A. Prieto -- V. Lifestyle exercise affecting neurological structure and function in older adults. Synergistic effects of combined physical activity and brain training on neurological functions / T.M. Shah and R.N. Martins -- Physical activity : effects of exercise on neurological function / R. Beurskens and M. Dalecki -- Update of nutritional antioxidants and antinociceptives on improving exercise-induced muscle soreness / N. Leelayuwat -- Effects of exercise-altered immune functions on neuroplasticity / A.L. Aral and L. Pinar.
Includes bibliographical references and index.
Keywords: Cognition -- Effect of exercise on; Aging -- Physiological aspects; Brain -- Wounds and injuries -- Exercise therapy; Exercise -- Physiological aspects; Neurology